Binge eating disorder and medical comorbidities in bariatric surgery candidates. Issue 5 (16th March 2015) - Mitchell, James E.; King, Wendy C.; Pories, Walter; Wolfe, Bruce; Flum, David R.; Spaniolas, Konstatinos; Bessler, Mark; Devlin, Michael; Marcus, Marsha D.; Kalarchian, Melissa; Engel, Scott; Khandelwal, Saurobh; et al.
ABSTRACT Objective To determine whether binge eating disorder (BED) status is associated with medical comorbidities in obese adults scheduled for bariatric surgery. Method The study utilized Longitudinal Assessment of Bariatric Surgery‐2 data obtained from six clinical centers around the United States. This is a well‐phenotyped cohort of individuals who were evaluated within 30 days before their scheduled surgery using standardized protocols. In the cohort, 350 participants were classified as having BED and 1, 875 as not having BED (non‐BED). Multivariable logistic regression was used to determine whether BED status was independently related to medical comorbidities. As an exploratory analysis, significance was based on nominal p‐values (p < .05). Holm's‐adjusted p‐values were also reported. Results After adjusting for age, sex, education, and body mass index, BED status was found to be independently associated with four of the 15 comorbidities (i.e., impaired glucose levels (odds ratio [OR] = 1.45 (95% confidence interval [CI]: 1.12–1.87)), high triglycerides (OR = 1.28 (95% CI: 1.002–1.63)), and urinary incontinence (OR = 1.30 (95% CI: 1.02–1.66)), all being more common among the BED sample, and severe walking limitations being less common in the BED sample (OR = 0.53 (95% CI: 0.29–0.96)). With further adjustment for psychiatric/emotional health indicators, BED status was independently associated with three comorbidities (impaired glucose levels (OR = 1.36 (95% CI: 1.04–1.79)), cardiovascular disease (OR = 0.50 (95% CI: 0.30–0.86)), and severe walking limitations (OR = 0.38 (95% CI: 0.19–0.77)). However, Holm's‐adjusted p‐values for all variables were greater than .05. Discussion The results suggest the possibility of a contribution of BED to risk of specific medical comorbidities in severely obese adults. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:471–476)